Video feedback intervention: a case series in the context of childhood hearing impairment - James, Deborah M.; Wadnerkar-Kamble, Meghana B.; Lam-Cassettari, Christa (John Wiley & Sons, 2012)
Background: Recent research shows that parental sensitivity can explain a significant and unique amount of growth in speech and language outcomes in children with cochlear implants. In this intervention study we explored the impact of an intervention designed to support parental sensitivity on children's communication development.